Drivers' calibration in self-evaluated performance: The role of task-related workload and scale specificity. (September 2016) - Horrey, William J.; Lesch, Mary F.; Liang, Yulan
Drivers tend to hold favorable or optimistic views of their skills and abilities (e.g., Horswill et al., 2004), which can lead to situations where over-confident drivers are ill-equipped (Gregersen, 1996). In addition to general self-evaluations of skills, drivers can also make erroneous estimates of their own performance and of current task demands, possibly leading to poor decisions or failures to adjust behavior to mitigate risk (e.g., Horrey et al., 2015). Gaps between perceptions, self-evaluations and objective measures have been likened to the notion of calibration .